2007
DOI: 10.1002/ijc.22626
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase and dihydropyrimidine dehydrogenase mRNA expression after administration of 5‐fluorouracil to patients with colorectal cancer

Abstract: This study explores the effect of 5-fluorouracil (5FU) exposure on mRNA levels of its target enzyme thymidylate synthase (TS) and the rate-limiting catabolic enzyme dihydropyrimidine dehydrogenase (DPD) in tumors of colorectal cancer patients. TS and DPD mRNA levels were determined in primary tumor and liver metastasis samples from patients who were either not pretreated (n 5 29) or given one presurgery bolus of 5FU (n 5 67). In both groups a wide variation in TS mRNA levels was observed. Median TS mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…In agreement with this hypothesis and with the observed increase in TS mRNA expression, as detected previously with pemetrexed and 5-FU Mauritz et al, 2007), TS protein expression and catalytic activity in cell extracts were enhanced after pemetrexed exposure.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with this hypothesis and with the observed increase in TS mRNA expression, as detected previously with pemetrexed and 5-FU Mauritz et al, 2007), TS protein expression and catalytic activity in cell extracts were enhanced after pemetrexed exposure.…”
Section: Discussionsupporting
confidence: 91%
“…TS, as an RNA-binding protein, also regulates its own synthesis by impairing the translation of its mRNA, whereas the binding to a specific inhibitor leads to upregulation of TS protein (Chu et al, 1991). In agreement with this hypothesis, as well as with the observed increase in TS mRNA expression, as previously detected with pemetrexed and 5-fluorouracil (5-FU) (Peters et al, 2002;Mauritz et al, 2007), TS protein expression in cell extracts was enhanced after pemetrexed exposure. However, this study also shows that enzastaurinpemetrexed combination significantly inhibited the activity of TS, potentially leading to synergistic drug interaction.…”
Section: Discussionsupporting
confidence: 83%
“…methylenetetrahydrofolate reductase gene polymorphisms). In addition to the fact that TS is the target enzyme of 5-fluorouracil, it has been observed that TS levels may be dynamic, with upregulation after fluoropyrimidine exposure (Uchida et al, 2004a, b;Mauritz et al, 2007). In particular, this effect was described in liver metastases from colorectal cancer in patients who received bolus 5-fluorouracil (Mauritz et al, 2007).…”
Section: Pharmacogenetics In Liver-only Metastatic Cancer F Graziano mentioning
confidence: 99%
“…In addition to the fact that TS is the target enzyme of 5-fluorouracil, it has been observed that TS levels may be dynamic, with upregulation after fluoropyrimidine exposure (Uchida et al, 2004a, b;Mauritz et al, 2007). In particular, this effect was described in liver metastases from colorectal cancer in patients who received bolus 5-fluorouracil (Mauritz et al, 2007). Therefore, TS polymorphisms may influence the outcome to 5-fluorouracil chemotherapy, not only for their role in determining different baseline levels of TS activity (Marsh, 2005), but also for modulating the enhancement of TS levels in response to 5-fluorouracil.…”
Section: Pharmacogenetics In Liver-only Metastatic Cancer F Graziano mentioning
confidence: 99%